PERANCANGAN ULANG TUTUP KALENG MAKANAN YANG AMAN - Lumban Tungkup, Fairizal; Sirait, Ganda (Computer Science and Industrial Engineering, 2023)
PT ABC is a manufacturing company engaged in canned food products. PT ABC produces several types of ready-to-eat food cans ranging from small to large sizes. Based on field studies, several problems were found in the can lid, where the can lid is often difficult to open, causing pain when opening the can lid. Another problem is the side of the can cover that is too sharp, causing cuts when hit by the side of the can cover when taking food. Therefore, it is necessary to redesign a safe food can lid to maintain user safety. The method used in this research is the NIDA method (Need, Idea, Decision, and Action). Based on the research results, there are 2 alternative forms of can lid design. The first alternative provides an increase in the distance between the puller and the lid of the can by 2mm and adds a curve to the side of the can cover in the form of a radius of 0.3mm. While the second alternative adds a distance between the puller and the lid of the can by 2mm and adds an arch on the side of the can cover in the form of an angle of 60 °. Based on the results of the analysis of the two alternatives, the first alternative was chosen as a safe form of can lid design.